Non-contrast and portal venous phase computed tomography in breast cancer hepatic metastases: comparison of tumor measurements and impact on response assessment. (February 2021) - Flemming, Brian; Kovacs, Mark D; Hardie, Andrew; Picard, Melissa; Burchett, Philip F; Collins, Heather; Sheafor, Douglas H
Background: For many common malignancies, including breast cancer, evaluation for metastatic disease using multiphase computed tomography (CT) has fallen out of favor and been replaced by studies performed only in the portal venous phase. However, differences in tumor vascularity could produce differences in appearance on post-contrast imaging. Purpose: To assess non-contrast phase and portal venous phase computed tomography in detection and measurement of hepatic metastases from breast carcinoma. Materials and Methods: A total of 75 CT scans from 52 breast cancer patients were independently assessed by three body imagers for lesion presence, number and size. Readers randomly assessed portal venous phase or combined phase images at one session with cross-over reads performed four to six weeks later. Results: In the 58% of cases where index lesions measured larger on combined phase, the mean difference in lesion size was 5.7 mm. In this group, combined phase reads demonstrated an 8.4 mm increase in sum of largest diameters, and a mean percentage sum of largest diameters increase of 19% compared to portal venous phase-only reads. Conclusion: Addition of non-contrast phase images results in increased index lesion size in most patients with hepatic metastases from breast cancer. If only the portal venous phase is utilized, there is potential for incorrectly diagnosing disease progression on follow-up due to underestimation of lesion size.